Establishment of a novel indicator of pyroptosis regulated gene transcription level and its application in pan-cancer - Xu, Jin-Zhou; Xia, Qi-Dong; Sun, Jian-Xuan; Liu, Chen-Qian; Lu, Jun-Lin; Xu, Meng-Yao; An, Ye; Xun, Yang; Liu, Zheng; Hu, Jia; Li, Cong; Wang, Shao-Gang (Scientific reports, 2023)
Pyroptosis is a type of programmed cell death and plays a dual role in distinct cancers. It is elusive to evaluate the activation level of pyroptosis and to appraise the involvement of pyroptosis in the occurrence and development of diverse tumors. Accordingly, we herein established an indicator to evaluate pyroptosis related gene transcription levels based on the expression level of genes involved in pyroptosis and tried to elaborated on the association between pyroptosis and tumors across diverse tumor types. We found that pyroptosis related gene transcription levels could predict the prognosis of patients, which could act as either a favorable or a dreadful factor in diverse cancers. According to signaling pathway analyses we observed that pyroptosis played a significant role in immune regulation and tumorigenesis and had strong links with other forms of cell death. We also performed analysis on the crosstalk between pyroptosis and immune status and further investigated the predictive potential of pyroptosis level for the efficacy of immunotherapy. Lastly, we manifested that pyroptosis status could serve as a biomarker to the efficacy of chemotherapy across various cancers. In summary, this study established a quantitative indicator to evaluate pyroptosis related gene transcription levels, systematically explored the role of pyroptosis in pan-cancer. These results could provide potential research directions targeting pyroptosis, and highlighted that pyroptosis may be used to develop a novel strategy for the treatment of cancer.